Thermal expansion of solid solutions Kr-CH₄ at temperatures of liquid helium - Aleksandrovskii, A.N.; Gavrilko, V.G.; Dolbin, A.V.; Esel`son, V.B.; Manzhelii, V.G.; Udovidchenko, B.G. (Физика низких температур, 2003)
A negative contribution of the CH₄ impurity to the thermal expansion of the solution has been revealed in the dilatometric studies of solid Kr + 0.76% CH4, Kr + 5.25% CH₄, and Kr + 10.5% CH₄ solutions at 1-23 K. It is shown that the negative contribution results from changes in the occupancy of the ground state of the A-modifications of isolated CH₄ molecules. Assuming that the CH₄ impurity singles and clusters contribute to the thermal expansion independently, we can estimate their contributions. The contribution of the singles to the thermal expansion of the solid solution is negative. The energies of the first excitational rotational states were determined for singles and two-body and three-body clusters of the CH₄ molecules.